Gas production from different classes of hydrate reservoirs. Issue 11 (3rd June 2017) - Li, S.; Jiang, X.; Li, Q.
ABSTRACT: A three-dimensional numerical model for gas production from hydrate reservoirs is developed, which considers the flow of multiphase fluid, conductive and convective heat transfer, and intrinsic kinetics of hydrate dissociation. Three components (gas, water, and hydrate) and three phases (gas, water, and hydrate) are considered in the model. Based on the model, gas production at the constant and same pressure from three different classes of hydrate reservoirs (Class I, Class II, and Class III) is compared. The simulation results suggest that gas production from Class I hydrate reservoir appears to be simpler and faster by depressurization. Gas production from Class II and Class III hydrate reservoirs are recommended by the combination of heat injection and depressurization. Results of gas production simulations can provide a theoretical basis for the development of hydrates in the future.